EFFECT OF LEADERSHIP STYLE ON PERFORMANCE OF EMPLOYEES PT LINTAS MEDIATAMA BANDUNG - Yani Restiani Widjaja; Rani Rahmayani; Andhita Dian Dini (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2019)
ABSTRACT The purpose of this study was to determine and analyze leadership style, employee performance and the influence of leadership style on the performance of employees of PT Lintas Mediatama Bandung. This study uses a non probability sampling technique with a type of census. The population in this study were thirty employees of PT Lintas Mediatama Bandung. All population members are used as samples. Data collection methods are divided into primary data and secondary data. primary data collection using observation, questionnaires, and interviews. Secondary data collection uses literature studies and scientific journal references. Test of research instruments such as frequency calculation, validity and reliability test the author uses SPSS version 20. The results of the study show that there is a relationship between leadership style and employee performance. The leadership style has a positive influence on employee performance. Key words: leadership style, employees performance